Faults Detection in a Photovoltaic Generator by Using Matlab Simulink and the chipKIT Max32 Board - Riadh Khenfer; Mohamed Mostefai; Seddik Benahdouga; Mounir Maddad (International Journal of Photoenergy)
This paper presents a laboratory with equipment and an algorithm for teaching graduate students the monitoring and the diagnosis of PV arrays. The contribution is the presentation of an algorithm to detect and localize the fault, in photovoltaic generator when a limited number of voltage sensors are used. An I-V curve tracer using a capacitive load is exploited to measure the I-V characteristics of PV arrays. Such measurement allows characterization of PV arrays on-site, under real operating conditions, and provides also information for the detection of potential array anomalies. This I-V curve tracer is based on a microcontroller board family called chipKIT Max32 which is a popular platform for physical computing. A user program can be developed visually on a PC side via the graphical user interface (GUI) in Matlab Simulink, where the chipKIT Max32 of Digilent which is a low-cost board is designed for use with the Arduinompid software. The obtained results from the partial shade default showed the effectiveness of the proposed diagnosis method and the good functioning of this board with the Matlab/Simulink environment.